Effect of transcranial direct current stimulation (tDCS) and transcutaneous electrical nerve stimulation (TENS) in knee osteoarthritis - Chaturvedi, Rekha; Joshi, Shabnam (Physiotherapy quarterly, 2021)
Introduction To compare the effectiveness of transcranial direct current stimulation (tDCS) and transcutaneous electrical nerve stimulation (TENS) when used in combination or in isolation on pain, function, and quality of life in primary knee osteoarthritis. Methods A 4-arm parallel group, participant-blinded, placebo-controlled randomized trial was performed. Patients with chronic knee osteoarthritis as per the American College of Rheumatology criteria were eligible. The lottery method was used for randomization and blocked randomization served to ensure an equal number of patients in each group. The participants were allocated to 4 groups and received tDCS and TENS either in combination or in isolation. Pain, function, and quality of life were measured with a visual analogue scale, 6-minute walk test, and Knee Injury and Osteoarthritis Outcome Score, respectively. The subjects were blinded to group allocation. The outcome measures were evaluated at baseline and day 5, 8, and 20 after the intervention. Data were analysed with the SPSS (version 21.0) software. Results On implementing the inclusion and exclusion criteria, 72 participants were enrolled in this trial; 69 of them completed the protocol. There was a significant reduction in pain in all the 3 experimental groups as compared with the control group. The maximum reduction in pain was seen in the group receiving active tDCS and active TENS at week 6. Conclusions The combination of tDCS and TENS along with strengthening exercises is effective in reducing pain in knee osteoarthritis.